2022
DOI: 10.1007/s11033-022-07690-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 expression is associated with pulpitis progression by targeting SHIP1

Abstract: Pulpitis is a commonly seen oral in ammation condition in clinical practice, it can cause much pain for the patient and may induce infections in other systems. Much is still unknown for the pathogenic mechanism of pulpitis. In this work, we discovered that the expression of miR-155 was associated with dental pulpal in ammation both in vivo and in vitro. Experiments on odontoblast cell line MDPC-23 showed miR-155 could act as a positive regulator by increasing the production of pro-in ammatory cytokines IL-1β a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Due to the absence of effective and harmless analgesia, pulpitis, characterized by a high morbidity rate and severe symptoms, imposes a signi cant physical and mental burden on affected patients 30 . Current clinical treatments for pulpitis pain are root canal therapies, although fairly effective, resulting in irreversible pulp damage and compromised long-term prognosis, underscoring the imperative need to comprehend the mechanism of pulpitis pain 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of effective and harmless analgesia, pulpitis, characterized by a high morbidity rate and severe symptoms, imposes a signi cant physical and mental burden on affected patients 30 . Current clinical treatments for pulpitis pain are root canal therapies, although fairly effective, resulting in irreversible pulp damage and compromised long-term prognosis, underscoring the imperative need to comprehend the mechanism of pulpitis pain 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR‐155 appears to regulate MSC immunoregulatory properties as pro‐inflammatory agent (Onodera et al, 2017; Xu et al, 2013) and miR‐155 showed a significant promoting effect on pulpitis (Ayadilord et al, 2021; Kim et al, 2018). But according to Li et al, the expression of miR‐155 in LPS‐MDPC23 was downregulated (Li et al, 2022). In addition, the expression of miR‐155 was downregulated in LPS‐gingival fibroblasts compared to normal gingival fibroblasts, and there appeared to be little change in dental pulp and periodontal ligament fibroblasts (Sipert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…SEMA3A can interact with microRNA‐155 (miR‐155), which has been found to be significantly upregulated in AP (Yue et al, 2016). miR‐155 exerts a pro‐inflammatory function in various tissues (Bala et al, 2016; Jiang et al, 2019; Li et al, 2022). Excessive expression of miR‐155 may affect inflammatory progression in AP by directly restraining SEMA3A (Yue et al, 2016).…”
Section: Sema3a In Pulpitis and Apmentioning
confidence: 99%